Peran Riset Dalam Meningkatkan Kualitas Pendidikan IPA - Moh. Amien (Universitas Negeri Malang, 2016)
The teaching of science is in many instances resorting to memorization. It is imperative to alter this kind of teaching of science such that it concerns with comprehension, human exixtence, and society. Research can enhance the way science is taught to the students while the achievement of the study of science among students.